Evidence-based clinical practice guidelines for inflammatory bowel disease - Matsuoka, Katsuyoshi; Kobayashi, Taku; Ueno, Fumiaki; Matsui, Toshiyuki; Hirai, Fumihito; Inoue, Nagamu; Kato, Jun; Kobayashi, Kenji; Kobayashi, Kiyonori; Koganei, Kazutaka; Kunisaki, Reiko; Motoya, Satoshi; et al. (Journal of gastroenterology, 2018)
Inflammatory bowel disease (IBD) is a chronic disorder involving mainly the intestinal tract, but possibly other gastrointestinal and extraintestinal organs. Although etiology is still uncertain, recent knowledge in pathogenesis has accumulated, and novel diagnostic and therapeutic modalities have become available for clinical use. Therefore, the previous guidelines were urged to be updated. In 2016, the Japanese Society of Gastroenterology revised the previous versions of evidence-based clinical practice guidelines for ulcerative colitis (UC) and Crohn’s disease (CD) in Japanese. A total of 59 clinical questions for 9 categories (1. clinical features of IBD; 2. diagnosis; 3. general consideration in treatment; 4. therapeutic interventions for IBD; 5. treatment of UC; 6. treatment of CD; 7. extraintestinal complications; 8. cancer surveillance; 9. IBD in special situation) were selected, and a literature search was performed for the clinical questions with use of the MEDLINE, Cochrane, and Igaku Chuo Zasshi databases. The guidelines were developed with the basic concept of the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. Recommendations were made using Delphi rounds. This English version was produced and edited based on the existing updated guidelines in Japanese.